Impaction bone grafting for acetabular bone defects replacement in revision hip arthroplasty: biomechanical aspects - Vadim N. Golnik; Natalia V. Fedorova; Alexey Y. Larichkin; Svetlana V. Boyko; Andrey A. Panchenko; Alexandr M. Kosinov; Vladimir A. Peleganchuk; Vitaliy V. Pavlov (Travmatologiâ i Ortopediâ Rossii)
Background. The leading role in long-term survival of the prosthesis installed using impaction bone grafting is given to the mechanical properties of the graft.